PP.34.13: THE CAPILLARY RAREFACTION IS ASSOCIATED TO REDUCED CEREBRAL ARTERIAL COMPLIANCE SINCE THE INITIAL HYPERTENSIVE STATE WITH A SLIGHT INCREASE OF THE INTIMA MEDIA THICKNESS. (June 2015) - Nazzaro, P.; Schirosi, G.; Mezzapesa, D.; De Benettis, L.; Federico, F.
Abstract : Objective: Mean cerebral artery (MCA) compliance has been associated with the central blood pressure properties and microcirculatory assessment. Aim of the study was to discern the relationship between the indices of capillary rarefaction and cerebral arterial functional markers in patients with marginal increase of structural damage at the initial state of hypertension. Design and method: Sixty-two male adult (55 ± /7y) untreated recently diagnosed very mild hypertensives (137 ± 5/88 ± 8) underwent carotid and transcranial echodoppler to determine, respectively, carotid intima media thickness, as structural subclinical index of arterial damage, and MCA Pulsatility (PI) e Resistivity (RI) indices and measure of the aortic augmentation index (AIx). Then, they underwent videocapillaroscopy of the middle and distal phalangeal skin of the 2nd, 3rd and 4th finger of the non-dominant hand during baseline (CAP) and venous congestion (CVC) obtaining capillary recruitment (REC) as indices of microcirculatory structural damage. Patients were divided in two equal group in order of higher (Hi) and lower (Lo) IMT. Results: Patients showed a similar metabolic assessment and ambulatory blood pressure monitoring.. The findings show significant characteristics (m ± s.d.. * :p < .05, ** :p < .01, *** :p < .001 vs LoIMT). Pearson test, adjusted for metabolic assessment and hypertensive state, demonstrate the association between AIx and PI ACM (.373*), RI ACM (.391*) and CVC (-.347*) in HiIMT. Figure. No caption available. Conclusions: The findings show that a slight increase of IMT shows a significant association to both cerebral arterial compliance and microvascular damage, which appears, and perhaps preceding, the structural subclinical arterial damage at the very early hypertensive state. Further studies are necessary.